Delayed neuropsychiatric sequelae of carbon monoxide poisoning : a case report / Nurul Azreen Hashim … [et al.] - Hashim, Nurul Azreen; Shuib, Norley; Mohamed, Salina; Ling, Shiao Ling; Mat Nor, Khariah (Faculty of Medicine, 2016)
Delayed neuropsychiatric sequelae is an important condition which commonly occur during recovery from acute carbon monoxide poisoning. Typical presentation would be apathy, disorientation, amnesia, hypokinesia, bizarre behavior, insomnia and neurological manifestations such as gait disturbance, hypertonia and tremor. We report here a case of a man presented with delayed neuropsychiatric sequelae one month after the carbon monoxide poisoning in his suicidal attempt. He presented with the typical presentation and diagnosis confirmed with the MRI findings. His MRI showed abnormal signal in subcortical hemisphere white matter of both temporo-fronto-parietal-occipital regions along the insula and both globus pallidus. He was treated with Olanzapine, Fluvoxamine, Chlorpromazine and Levodopa and his condition slowly improved. It is important for clinicians to recognize the symptoms and risk factors to develop delayed neuropsychiatric sequelae in patients who previously had carbon monoxide poisoning.